Haemogram in yak (Poephagus grunniens L.) during parturition - SARKAR, M; DAS, B C; MANDAL, D B; DAS, D N; MOHANTY, T K; SINGH, B P; PAL, R N; RAY, S (The Indian Journal of Animal Sciences, 2012)
Haemogram in respect of total erythrocyte count (RBC), haemoglobin (Hb), packed-cell volume (PCV), total leukocyte count (WBC) and differential leukocyte counts (DLC) in 7 female yaks at 3 consecutive days pre-parturient, postÂ· parturient and on the day of parturition were determined. RBC count, per cent Hb , PCV and WBC counts substantially increased on the day of parturition. The decline in the values was observed within 24 hr. Neutrophils and lymphocytes increased on day of parturition and then started declining slowly and reached preparturient values within 3 days.